Neonatal outcome of infants with umbilical cord arterial pH less than 7 - So Ling Lau; Zara Lin Zau Lok; Shuk Yi Annie Hui; Genevieve Po Gee Fung; Hugh Simon Lam; Tak Yeung Leung (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Umbilical arterial pH of less than 7 is often used as the threshold below which the risks of neonatal death and adverse long‐term neurological outcomes are considered to be higher. Yet within the group with pH <7, the risks have not been further stratified. Here, we aimed to investigate the predictors of adverse long‐term outcomes of this group of infants. Material and methods This was a retrospective study of 248 infants born after 34 weeks of gestation in a tertiary obstetric unit, between 2003 and 2017, with cord arterial pH <7 or base excess ≤−12 mmol/L at birth. The infants were categorized into two groups: (1) intact survivors, or (2) neonatal/infant deaths or cerebral palsy or developmental delay. The umbilical arterial pH and base excess levels, Apgar scores, mode of delivery, gestational age, small for gestational age, birth in the era before the implementation of neonatal hypothermic therapy, and the presence of a known sentinel event, were compared between the groups using univariate analysis followed by multivariate analysis. Results Among the 248 infants, there were 222 intact survivors (89.5%) and 26 infants with poor outcomes (10.5%), including eight deaths (3.2%) and 18 (7.3%) with cerebral palsy and/or developmental delay. Univariate analysis showed that infants with adverse outcomes had significantly lower cord arterial pH (6.85 vs 6.95, with p < 0.001), lower cord arterial base excess (−19.95 vs −15.90 mmol/L, p < 0.001), a higher proportion of having AS at 5 min <7 (65.4% vs 13.1%, p < 0.001), and a higher proportion of having a sentinel event (34.6% vs 16.7%, p = 0.034). Multivariate analysis confirmed cord arterial pH of <6.9 and an Apgar score at 5 min <7 as independent prognostic factors (the adjusted odds ratios were 4.64 and 6.62, respectively). The risk of adverse outcome increased from 4.3% when the arterial pH was between 6.9 and <7, to 30% when the pH was <6.9. Conclusions Infants born with umbilical artery pH <7 still have a high chance of 89.5% to become intact survivors. A cord arterial pH of <6.9 and an Apgar score at 5 min <7 are independent prognostic factors for neonatal/infant death or adverse long‐term neurological outcomes.